2009
DOI: 10.1242/jcs.032102
|View full text |Cite
|
Sign up to set email alerts
|

Apical membrane maturation and cellular rosette formation during morphogenesis of the zebrafish lateral line

Abstract: Tissue morphogenesis and cell sorting are major forces during organ development. Here, we characterize the process of tissue morphogenesis within the zebrafish lateral line primordium, a migratory sheet of cells that gives rise to the neuromasts of the posterior lateral line organ. We find that cells within this epithelial tissue constrict actin-rich membranes and enrich apical junction proteins at apical focal points. The coordinated apical membrane constriction in single Delta D-positive hair cell progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…The Fgfr-Ras-MAPK signaling cascade is required for apical constriction in leading pLLp cells Apical constriction has been suggested to underlie pLLp rosette formation (Hava et al, 2009;Chitnis et al, 2012). Cell shape analysis during live imaging of rosette formation revealed that, over a 1-hour period, columnar cells become apically constricted as nascent rosettes form (Fig.…”
Section: Results and Discussion Rosette Formation Is Dependent On Thementioning
confidence: 99%
“…The Fgfr-Ras-MAPK signaling cascade is required for apical constriction in leading pLLp cells Apical constriction has been suggested to underlie pLLp rosette formation (Hava et al, 2009;Chitnis et al, 2012). Cell shape analysis during live imaging of rosette formation revealed that, over a 1-hour period, columnar cells become apically constricted as nascent rosettes form (Fig.…”
Section: Results and Discussion Rosette Formation Is Dependent On Thementioning
confidence: 99%
“…Cells of the primordium express E-cadherin and show foci of the TJ protein ZO1 and aPKC at the center of the tightly packaged primordium (Revenu et al 2014), similar to mature epithelium. On the other hand, cells particularly located at the edge of this cell group display typical mesenchymal characteristics, such as reduced apicobasal polarity and the presence of highly dynamic actin-rich lamellipodia-like protrusions at the basal interactions to the tissue (Lecaudey et al 2008;Hava et al 2009). Thus, within the same moving cell group, different interaction types are found, with strong cell -cell adhesions at the center of the migrating cluster and more mesenchymal cells with weaker adhesions but higher actinmediated mobility at the periphery and in leader cells.…”
Section: Tissue Morphogenesis and Regenerationmentioning
confidence: 99%
“…Through a lateral inhibition process mediated by Notch-Delta signaling activity, one cell from a proneural cluster is specified as a neuroblast, while the rest of the cells in the cluster that have higher Notch signaling activity remain epithelial cells. During the formation of proneuromast rosettes in the zebrafish posterior lateral line primordium, morphogenesis is independent of cell fate-determining Notch-Delta signaling activity (Hava et al, 2009). In Drosophila embryos, it has been shown that overexpression of the Notch intracellular domain (NICD) leads to premature cell division in the ventral neuroectoderm (Hartenstein et al, 1994).…”
Section: Medial Myosin Pulses Are Required For the Apical Constrictiomentioning
confidence: 99%